Targeted Therapy and Immunotherapy for Non-small Cell Lung Cancer with Brain Metastasis - Qi SONG; Shunchang JIAO; Fang LI (Chinese Journal of Lung Cancer, 2016)
Brain metastasis, a common complication of non-small cell lung cancer (NSCLC) with an incidence rate of 30%-50%, significantly affects the patients’ quality of life. The prognosis of patients of NSCLC with brain metastasis is extremely poor, the average median survival is only 1 m-2 m without treatment. The targeted therapy based on lung cancer driven gene is a new treatment. Besides, the immunotherapy which can enhance the effect of anti-cancer by simulating the immune system is a new approach. The combination of targeted therapy and immunotherapy can greatly benefit patients in clinical work.